Cecilia Tossounian, La joven moderna in Interwar Argentina: Gender, Nation, and Popular Culture, 1920-1940, Gainesville, University of Florida Press, 2020, 165 páginas - Manzano, Valeria (2021)
Fil: Manzano, Valeria. Universidad Nacional de San Martín; Argentina.